Integration of Science and Religion in the Methodology of Holmes Rolston's Philosophy - Fauzi, Machfudz (El-Ghiroh : Jurnal Studi Keislaman, 2024)
The viewpoint that talks about religion and science is not a subject that will run out with the times. This is because the connection between the two fills space and time, and it is interesting to study and accelerate the correlation between the two clearly. In fact, these studies need to be developed in a concentrated manner among scholars, especially academics in universities. The basis of the correlation between the two is to provide reinforcement that science and religion/theology are two sides of a coin that are interrelated to explain each other between the levels of belief and rationality. Moreover, this answer, on the other hand, makes the assumption that science and religion cannot be united. Based on this description, we will try to think about how scientific integration between religion and science is not dichotomized with its own scientific building. As seen in Holmes Rolston's philosophical methodology, which seeks to explain the correlation between the study of theology and science, In his view, theology, or religion, and science can clearly grow and develop together, and there is even certainty of complementarity between them. By using the writing rules of a qualitative approach through a literature study or library research, this research seeks to upload Holmes Rolston's views regarding the integration of science and religion/theology. Because, in his view, religion and science are a response to the cyclotomy that seeks to answer that between the two is able to meet and complement from a methodology.